Fetisisme Ras Kaukasoid dan Ras Mongoloid Sebagai Strategi Pemasaran dalam Sinetron Indonesia - Yudhistira, Dimas; Priyatna, Aquarini; Mahzumi, Dade (PANGGUNG, 2014)
ABSTRACTÃÂ Popular culture that rises with industrialization influences the production of film in Indonesia. One of genres of IndonesiaÃ¢â¬â¢s film is soap opera. Soap opera has two sides, the first side as market com- modity and the second side as popular art, whichcategorized itself as kitsch. As producing their pro- duct, soap opera has to see trough the background of its society. This research used qualitative method. The research resultsmost of Indonesian are Malaya that have colonized by Caucasian and Mongolian before 1945 and after that. It causes eÃ¯Â¬â¬ect of fantasies that create the stereotype about Caucasian and Mongolian appearances. Stereotype makes Malaya have fetishism about Caucasian and MongolianÃ¢â¬â¢s appearance. Director of soap opera uses this kind of fetishism as appeal to audiences in Indonesia. Displaying the racial half-bred of body of actress and actor in soap opera is become one of marketing strategy to promote soap opera. This is why half-breed actress and actor always get the important role in Indonesian soap opera.ÃÂ Keywords: soap opera, kitsch, race, fetishismÃÂ ÃÂ ÃÂ ÃÂ ABSTRAKÃÂ Budaya populer yang tumbuh seiring dengan industrialisasi memengaruhi produksi per- filman di Indonesia. Salah satu genre perfilman di Indonesia adalah sinetron. Sinetron yang di- kategorikan sebagai produk seni kitsch memiliki dua kriteria yaitu sebagai komoditi seni yang populer dan sebagai komoditi dagang yang menghasilkan keuntungan ekonomis. Sebagai se- buah produk seni kitsch yang merupakan dasar pembuatan karyanya adalah selera masyarakat kebanyakan maka sinetron harus jeli dalam melihat keadaan dan latar belakang masyarakat. Penelitian ini menggunakan metode kualitatif. Hasil penelitian ini menggambarkan masyara- kat Indonesia yang merupakan ras Melayu telah dÃÂ³ajah oleh ras Kaukasoid dan Mongoloid sebelum tahun 1945 dan setelahnya. Efek dari penjajahan ini adalah ras Melayu telah ditanami fantasi yang menjadi stereotip mengenai ras Kaukasoid dan Mongoloid yang berakhir dengan fetisisme. Fetisisme ini dÃÂ³adikan sebagai strategi pemasaran oleh produser dan sutradara un- tuk menarik antusiasme calon penonton sinetron. Caranya dengan menampilkan aktor dan aktris Melayu keturunan Kaukasoid dan Mongoloid sebagai pemeran utama.ÃÂ Kata kunci: sinetron, seni kitsch, ras, fetisisme